A fast SALLE GC–MS/MS multi-analyte method for the determination of 75 food packaging substances in food simulants. (1st November 2021) - Tsochatzis, Emmanouil D.; Lopes, Joao Alberto; Gika, Helen; Dalsgaard, Trine Kastrup; Theodoridis, Georgios
Highlights: A fast and sensitive method with simple sample preparation is presented. Use of multiple reaction monitoring (MRM) acquisition. Application of deuterated internal standards. Simple salt-assisted liquid–liquid extraction (SALLE). Applicability of the method to food packaging materials. Abstract: A simple and fast method was developed for the simultaneous determination of 75 plastic food contact material (FCM) in liquid food simulants, at levels of a few ng g −1 . The method employs an optimised salt-assisted liquid–liquid extraction for all EU-regulated ethanol/H2 O food simulants, in the presence of 10% NaCl (simulants A and C) or 5% NaCl (simulant D1), and dichloromethane as the extracting solvent. Gas chromatography with triple-quad MS operating in multiple reaction monitoring acquisition was used, applying isotope dilution with selected deuterated compounds. Adequate sensitivity was demonstrated for all analytes. The results also showed sufficient accuracy for the majority of substances, with recoveries of 70–120% and repeatability (expressed as relative standard deviations, RSDs) smaller than 15%. The method was applied to the analysis of FCM multilayer items after undergoing migration testing according to the specifications of the current EU legislation in force.